2020
DOI: 10.28998/rca.v18i1.7388
|View full text |Cite
|
Sign up to set email alerts
|

RESPOSTA DE SORGO INOCULADO COM Azospirillum brasilense A DOSES DE NITROGÊNIO EM COBERTURA

Abstract: <p>Estirpes de <em>Azospirillum brasilense</em> conseguem fornecer parte do nitrogênio que as gramíneas necessitam. Objetivou-se avaliar o efeito combinado da inoculação de <em>A. brasilense</em> e nitrogênio sobre as características agronômicas do sorgo granífero e a população de bactérias diazotrópicas nas raízes. O trabalho foi composto por duas etapas: 1- Ensaio a campo: T1= 200 Kg.ha<sup>-1</sup> de ureia (U), T2= 300 mL ha<sup>-1 </sup>de inoculante +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 9 publications
1
4
0
2
Order By: Relevance
“…Sorghum PH was significantly bigger with A. brasilense inoculation (Table 3). This result corroborates other studies that also found an increase in the height of sorghum plants with A. brasilense inoculation (Nakao et al, 2014;Mortate et al, 2020;Barros, 2022). The bigger height of the inoculated sorghum plants is mainly attributed to the ability of this bacterium to biologically fix nitrogen and produce growth-stimulating phytohormones (auxins, cytokinins, and gibberellins) (Cassán et al, 2020;Canepelle, 2023).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Sorghum PH was significantly bigger with A. brasilense inoculation (Table 3). This result corroborates other studies that also found an increase in the height of sorghum plants with A. brasilense inoculation (Nakao et al, 2014;Mortate et al, 2020;Barros, 2022). The bigger height of the inoculated sorghum plants is mainly attributed to the ability of this bacterium to biologically fix nitrogen and produce growth-stimulating phytohormones (auxins, cytokinins, and gibberellins) (Cassán et al, 2020;Canepelle, 2023).…”
Section: Resultssupporting
confidence: 92%
“…Stem diameter (SD), PH, shoot dry mass (SDM), RDM, leaf area (LA), chlorophyll b (Cl b), and chlorophyll a (C1 a) showed no significant interaction between doses and inoculation, with only a single significant difference between inoculation for SD, PH, SDM, LA, Cl b, and Cl a. SD was significantly higher in sorghum plants inoculated with A. brasilense (Table 3). This can be attributed to mechanisms that promote growth and development, such as production of phytohormones, solubilization of phosphorus and potassium, and production of hydrolysis enzymes and siderophores (Araújo et al, 2012;Tan et al, 2014), as well as, to the nitrogen supply, coming from fixation by PGPR (Mortate et al, 2020). This result is important, as the reduction in diameter makes plants sensitive to lodging and breakage, negatively affecting crop harvest (May et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Mortate et al (2020) evaluating nitrogen rates in red latosol and using grain sorghum hybrid found a response up to a dose of 200 kg ha -1 of N. Mateus et al (2011) observed a response of grain sorghum intercropped with grass in a no-tillage system in the region of Botucatu, SP, Brasil, in dystrophic red latosol soils in which, in the first year of cultivation, the 50-50 kg ha -1 N splitting provided higher sorghum productivity, and this high dose may have been obtained because it was the first year of cultivation planting. Similar observations were found by Santos et al (2014) where they obtained in the work carried out in Sete Lagoas, MG, Brasil, in red distroferric latosol soils, the dose of N to obtain the maximum economic efficiency, considering sorghum CMSXS 7020, was of 60 kg ha -1 , while for CMSXS 652 the economic dose of N was approximately 40 kg ha -1 , and in the study by Rosolem et al (1985) where the researchers demonstrated the response of sweet sorghum to nitrogen fertilization, in a dystrophic purple latosol in the Botucatu region, SP, Brasil, obtained the best dose of 114 kg ha -1 of N.…”
Section: Introductionmentioning
confidence: 98%
“…O nitrogênio, compõe um dos nutrientes mais onerosos no processo produtivo de algumas culturas (ANDRADE et al, 2019), e nesse contexto as gramíneas necessitam de altas doses de adubação nitrogenada para produção (SCHUMACHER et al, 2021). Para as gramíneas, como: o milho, o trigo e o arroz, essa necessidade torna-se ainda mais evidente, sendo esse nutriente a principal base nutricional dessas plantas (NUNES et al, 2015;MORTATE et al, 2020). Um grande problema ocasionado pela alta demanda e fornecimento da adubação nitrogenada, pode ser o inadequado aproveitamento do nutriente pelas plantas, acarretando rendimento reduzido, perdas por lixiviação e volatilização, aumento nos custos, além dos prejuízos ambientais ocasionados na fabricação do produto, através da liberação de gases de efeito estufa (UBERT e SOLIGO, 2015;MORTATE et al, 2020).…”
Section: Introductionunclassified